Implementation science in nutrition practice: A review of the Consolidated Framework for Implementation Research. - Sivakumar, Bridve; Mak, Jordan; Bafagih, Salma; Arcand, JoAnne (Nutrition in Clinical Practice, 2025)
Many nutrition interventions and innovations are supported by strong evidence; however, their adoption, implementation, and long‐term sustainability in real‐world healthcare settings too frequently remain a challenge. Implementation science offers methodologies to equip practitioners with tools to identify and address the contextual factors that influence implementation success in health settings (e.g., adoption, implementation, sustainability). Among the various frameworks and theories used in implementation science, the Consolidated Framework of Implementation Research (CFIR) is one of the most widely used. The CFIR synthesizes constructs from multiple behavioral and implementation theories into a comprehensive tool that can be used to systematically assess the barriers and facilitators that influence implementation outcomes. The framework enables practitioners and researchers to identify context‐specific implementation determinants and to design tailored implementation strategies across diverse contexts and settings. Given its adaptability, the CFIR is highly relevant to the field of nutrition and dietetics to support sustained adoption and delivery of nutrition innovations (e.g., screening tools, educational programs, quality improvement initiatives); but it is relatively underutilized in nutrition practice. This article provides an overview of the CFIR and illustrates how it can be used to guide the implementation of nutrition innovations in clinical practice through two pragmatic case studies. We highlight the potential of the CFIR to be used as a guiding framework to advance the adoption, implementation, and sustainability of nutrition innovations and improve nutrition care and patient outcomes.